(untitled) (Advancements in Homeopathic Research, 2022)
Hepatitis B is a major health hazard around the globe becauseof its highly infectious nature. No alarming sign and symptoms in early stage of chronic infection are exhibited but lethal damage to the liver takes place in advance stage.The worst part is the non-availability of curative treatment in any system of medicine. The above fact makes a common belief in society that Hepatitis B is an incurabledisease. There are certain claims by homoeopathic physicians having treated cases of Hepatitis B. These are, however, neither documented on scientific parameters nor published in journals. To explore the possibility of efficacy of Homoeopathic medicines, a few patients suffering from Hepatitis B have been enrolled in Gaurang Clinic & Centre for Homoeopathic research, Lucknow fortreatment and assessment on modern parameters.The initial results are encouraging as the patients are not only clinically benefitted but have also shown reduction in Viral load.Some have even become seronegative.